Physical and Optical Properties of Al/Yb-dually incorporated CuS Particles Prepared by Facile Co-precipitation Process - Pakkawat Nimitnopphasit; Junkrajang Wattana; Thanaphon Kansaard; Wanichaya Mekprasart; Kanokthip Boonyarattanakalin; C.K. Jayasankar; Weerachon Phoohinkong (Thai Journal of Nanoscience and Nanotechnology, 2024)
Energy saving and management is considered as important aspects requiring relevant research and technological knowledge. Near infrared (NIR) shielding is an effective technology to reduce the energy consumption in the building that requires appropriate materials for specific shielding wavelengths. Copper (II) sulfide (CuS) is considered as an interesting p-type semiconductive material with good NIR shielding character and its optical property can be further enhanced by incorporation with proper dopants. This work reports on the facile synthesis of CuS particle via co-precipitation method. The influence of Al and Yb ions as the potential dopants on structural and optical properties are investigated by X-ray diffraction technique, field-emission scanning electron microscope, energy dispersive x-ray spectroscopy, and UV-VIS-NIR spectroscopy. Both Al and Yb dopants play significant roles on the modification of both physical and optical properties, especially in NIR spectra region. CuS with certain Al and Yb doping contents results in and considerable improvement in NIR shielding performance.
Keywords: Quantum Dots Synthesis And Properties; Chalcogenide Semiconductor Thin Films; Luminescence Properties of Advanced Materials